A high-transmittance packaging material for optical communication equipment and a preparation method thereof
By using a combination of polyurethane elastomer and ethylene-vinyl alcohol copolymer in the packaging materials of optical communication equipment, combined with terpene resin, phosphorus-containing flame retardant and glass fiber, the problem of yellowing and transparency reduction of the material after long-term use is solved, achieving high transparency and aging resistance.
Patent Information
- Application Number
- CN202410764708.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-14
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2044-06-14
AI Technical Summary
The packaging materials of existing optical communication equipment are prone to yellowing due to flame retardant pooling or resin oxidation after long-term use, resulting in a decrease in transparency and affecting aesthetics and environment.
A combination of polyurethane elastomer and ethylene-vinyl alcohol copolymer is used, and terpene resin, phosphorus-containing flame retardant and glass fiber are added to improve oxidation and aging resistance through hydrogen bonding and dense structure, and maintain high transparency.
In long-term use, the material can maintain high transparency, reduce yellowing, improve oxidation and aging resistance, and enhance aesthetics and environmental adaptability.
Smart Images

Figure BDA0004892077820000081 
Figure BDA0004892077820000091 
Figure BDA0004892077820000092
Abstract
Description
Technical Field
[0001] The present application relates to the field of optical communication equipment, and in particular to a high-transmittance packaging material for optical communication equipment and a preparation method thereof. Background Art
[0002] As optical communication equipment becomes more and more intelligent, efficient and modular, more and more intelligent optical communication equipment has entered thousands of households. The high requirements for aesthetics and safety indoors have also put forward better requirements for the packaging materials of optical communication equipment.
[0003] Existing optical communication materials are usually a blended rubber system of polyurethane elastomer and ethylene-vinyl acetate copolymer, which provides basic light transmittance, thereby ensuring its aesthetic performance in interior decoration, allowing it to be integrated with other decoration structures indoors. At the same time, the firmness of its packaging is also guaranteed to a certain extent. However, the flame retardant performance requires the additional addition of granular flame retardants to achieve, and the addition of flame retardants will cause the light transmittance of the above materials to deteriorate, thereby affecting its overall aesthetics. During long-term use, it will also turn yellow due to the precipitation of flame retardants in the system or the oxidation of the resin itself. Specifically, the rubber system becomes darker and yellower as a whole, thereby destroying the environment of interior decoration. Summary of the invention
[0004] In order to provide a plastic material with flame retardant properties that can maintain long-term high transparency to adapt to indoor decoration environments and achieve long-term high transparency effects, the present application provides a high-transparency packaging material for optical communication equipment and a preparation method thereof.
[0005] First, the present application provides a high-transmittance packaging material for optical communication equipment, which includes the following components in parts by mass:
[0006] Polyurethane elastomer 100 parts
[0007] Terpene resin 1-3 parts
[0008] Phosphorus-containing flame retardant 5-10 parts
[0009] 30-40 parts of ethylene-vinyl alcohol copolymer
[0010] Glass fiber 5-10 parts
[0011] Antioxidant 0.1-1 part
[0012] Compatibilizer 2-5 parts
[0013] The polyurethane elastomer is obtained by polymerizing polyester polyol and aromatic isocyanate compounds, wherein the polyester polyol contains polycarbonate diol accounting for 30 to 50% of the mass of the polyester polyol;
[0014] The isocyanate compound does not contain bromine atoms;
[0015] The diameter of the glass fiber is less than 5 μm.
[0016] In the above scheme, a scheme is adopted in which polyurethane elastomer is used as the main body and ethylene-polyvinyl alcohol copolymer is added. Since ethylene-vinyl alcohol copolymer has more hydroxyl groups, a more compact protective layer structure can be formed through hydroxyl bonding to improve the air tightness of the system. At the same time, since the polyurethane elastomer itself has good milk performance, in the above structure, after the polyurethane elastomer blocks the penetration of water, the hydroxyl structure in the ethylene-polyvinyl alcohol copolymer can form a compact insulating film structure, thereby keeping the oxygen permeation and water permeation in the whole system at a low level, thereby improving the overall oxidation resistance and aging resistance.
[0017] On the basis of the above, the polyurethane elastomer contains polycarbonate diol, which has a strong ability to form hydrogen bonds with polyvinyl alcohol, and uses aromatic isocyanate. Aromatic isocyanate is easier to form a barrier structure in the system than aliphatic isocyanate. Compared with aliphatic isocyanate system, aromatic isocyanate is more suitable for improving oxidation resistance in the system.
[0018] In the above system, the blended system formed by ethylene-vinyl alcohol copolymer and polyurethane elastomer has a better coating effect on phosphorus-containing flame retardants. Since ethylene-vinyl alcohol has good hydrogen bonding properties and the molecular chain is relatively soft, it can improve the dispersion performance of glass fiber and phosphorus-containing flame retardants without affecting the basic mechanical properties of the overall material, so that after long-term use, it can still maintain good transparency and reduce yellowing, thereby improving its appearance performance indoors.
[0019] In the system, glass fiber is selected as filler and reinforcing agent, and terpene resin is added to improve cohesion. Glass fiber and terpene resin can greatly improve the tensile strength and wear resistance of the system. At the same time, glass fiber itself has good transparency, so it has little effect on the light transmittance of the system.
[0020] Preferably, the number average molecular weight of the polycarbonate diol is 1000-3000.
[0021] The polycarbonate has a molecular weight of 2500 to 3000, which can provide a relatively long soft chain structure, can better form an elastomeric system in the system, and also has good compatibility with ethylene-vinyl alcohol copolymer.
[0022] Preferably, the molar content of ethylene segments in the ethylene-vinyl alcohol copolymer is 24-36%.
[0023] The ethylene content of the above-mentioned ethylene-vinyl alcohol copolymer is selected within a range that allows the ethylene-vinyl alcohol copolymer as a whole to have a relatively high hydroxyl content, while the hydroxyl content is not too high. Within this range, the system can have good sealing properties while also providing good water resistance and compatibility. Excessive vinyl alcohol chain content can lead to poor weather resistance and sealing properties of the system in a high humidity environment, thereby causing migration and agglomeration of the flame retardant.
[0024] Preferably, the number average molecular weight of the ethylene-vinyl alcohol copolymer is 30,000 to 36,000.
[0025] The ethylene-vinyl alcohol copolymer within this molecular weight range can improve the overall mechanical properties and aging resistance.
[0026] Preferably, it also includes 10 to 15 parts by weight of ultra-low density polyethylene.
[0027] Ultra-low-density polyethylene has a more branched structure, which can improve the elasticity and softness of the system, while having less impact on the sealing performance, making the overall structure moderately elastic and soft, and having better tensile strength.
[0028] Preferably, the polyester polyol is a combination of polycarbonate diol and saturated fatty acid polyester polyol.
[0029] In this system, fatty acid polyester polyol and polycarbonate diol are selected for copolymerization. The long aliphatic chain can improve the mixing uniformity of ethylene-vinyl alcohol copolymer in the packaging material, while reducing the rigidity of the system, and improving the resistance to stretching, rubbing and bending. After experiments, when the saturated fatty acid polyester polyol is selected from polyethylene glycol sebacate with double terminal hydroxyl groups, the overall mechanical properties are stronger.
[0030] More preferably, the number average molecular weight of the polyethylene glycol sebacate is 650-800.
[0031] Preferably, the phosphorus-containing flame retardant is polyphosphate.
[0032] Polyphosphate can be better dispersed in the above packaging material system and fully exert the flame retardant effect.
[0033] The present application also relates to a method for preparing the above-mentioned high-transmittance and high-packaging material, comprising the following steps: after mixing the raw materials, vacuum kneading and molding them at 160-170°C through a kneading machine, and then making the corresponding packaging structure through any one of encapsulation, injection molding, and extrusion.
[0034] In summary, the present application provides a high-transmittance packaging material for optical communication, which, through the combination of polyurethane elastomer and ethylene-vinyl alcohol copolymer, can provide strong oxidation resistance, aging resistance, and moisture resistance while ensuring the mechanical strength of the system. The flame retardant is not easy to agglomerate during long-term use, which ensures a high flame retardant effect while reducing the loss of light transmittance, and has better aesthetics when used indoors. DETAILED DESCRIPTION
[0035] The solution of the present application is further described through the following specific implementation methods.
[0036] In the present application, the polyurethane elastomer used can be obtained by copolymerization of polyester polyol and isocyanate. In this scheme, bromine-containing isocyanate is not used. Although bromine-containing isocyanate can make the prepared polyurethane elastomer have certain flame retardant properties, it is easy to introduce impurities, so its transparency is poor, which does not meet the original design intention of this scheme.
[0037] In this scheme, TDI is selected as isocyanate. In addition, the use of MDI or other isocyanates has little effect on the system performance.
[0038] In this scheme, the preparation method of polyurethane is as follows:
[0039] The polyester polyol is first mixed with a chain extender and a catalyst, and then isocyanate is added to the system to react through a one-step reaction method to obtain a polyurethane elastomer. The reaction temperature is controlled at 100°C. Based on 100 parts by mass of the polyester polyol, the chain extender is 1,4-butanediol, which is 5 parts by mass. The catalyst is an organic tin catalyst, specifically KOSMOS 16. The overall functionality of the isocyanate group and the hydroxyl group of the system is controlled at about 1:1.
[0040] In the following schemes, the polyester polyols used are of the types shown in Table 1.
[0041] Table 1
[0042] serial number type Number average molecular weight A1 Polyethylene glycol sebacate 650 A2 Polyethylene glycol sebacate 800 A3 Polyethylene glycol sebacate 1100 A4 Polyethylene glycol sebacate 2000 A5 Poly(hexanediol adipate) 700 A6 Poly(hexanediol adipate) 1000 A7 Polyethylene adipate 650 A8 Polyethylene adipate 750 A9 Polyethylene adipate 1000 A10 Polyethylene Succinate 550 A11 Polyethylene Succinate 750 B1 Polycarbonate diol 1400 B2 Polycarbonate diol 2500 B3 Polycarbonate diol 3000 B4 Polycarbonate diol 4500 C1 Polyethylene terephthalate 1600 C2 Polyethylene terephthalate 2550
[0043] In the following preparation examples, different polyester polyols or combinations of polyester polyols were used under the same preparation scheme, as shown in Table 2.
[0044] Table 2
[0045] Preparation Example No. Polyester polyol selection 1 A1 2 A3 3 A5 4 A6 5 A8 6 A11 7 B2 8 B3 9 50%A1+50%B1 10 50%A1+50%B2 11 50%A1+50%B3 12 50%A1+50%B4 13 30%A1+70%B3 14 10%A1+90%B3 15 70%A1+30%B3 16 50%A1+50%C1 17 50%A1+50%C2 18 50%A2+50%B2 19 30%A2+70%B2 20 50%A3+50%B3 21 50%A4+50%B3 22 50%A5+50%B3 23 50%A6+50%B3 24 50%A7+50%B3 25 50%A8+50%B3 26 50%A9+50%B3 27 50%A10+50%B3 28 50%A11+50%B3
[0046] In this application, the selected ethylene-vinyl alcohol copolymers are all commercially available products, and specific parameters can be customized. Specifically, the types of the selected ethylene-vinyl alcohol copolymers are shown in Table 3.
[0047] Table 3
[0048] serial number Vinyl content (%) Number average molecular weight EVOH-1 24 30000 EVOH-2 36 30000 EVOH-3 48 30000 EVOH-4 24 20000 EVOH-5 24 36000 EVOH-6 24 45000
[0049] It should be noted that among the above components, the number average molecular weights are all those of the target product. In fact, the number average molecular weight of the synthesized polymer may have an error of no more than 10%, but it will not have a significant impact on the performance as a whole.
[0050] For the following examples, the following detection methods were used to detect the products:
[0051] 1. Transparency test: With transparent PET as the substrate, refer to "GB2410 Transparency and Haze Test Method for Transparent Plastics" to determine the overall transparency.
[0052] 2. Tensile strength: Refer to ISO 37:2017 Rubber, vulcanized or thermoplastic. Tensile stress to determine the tensile strength and elongation at break of the above materials.
[0053] 3. Hardness: Tested by Shore hardness standard at 25℃.
[0054] 4. Moisture and heat resistance test: Aging for 480 hours at 75°C and 100% humidity, then take out and naturally cool to room temperature, and measure the transparency and tensile strength loss.
[0055] In addition, the following embodiments need to pass the flame retardancy test and have an afterflame time of less than 5 seconds before they are considered.
[0056] First, the following examples are set up, and different polyurethane elastomers and ethylene-vinyl alcohol copolymers in the above table are used for measurement.
[0057] In the following examples, the weight parts of each material are as follows:
[0058] Polyurethane elastomer 100 parts
[0059] 40 parts of ethylene-vinyl alcohol copolymer
[0060] 3 parts of terpene resin
[0061] 5 parts of phosphorus-containing flame retardant
[0062] Glass fiber 10 parts
[0063] Antioxidant 0.1 part
[0064] 5 parts of compatibilizer
[0065] 10 parts of ultra-low density polyethylene;
[0066] The phosphorus-containing flame retardant is polyphosphate, the glass fiber is commercially available low-boron glass fiber with an average diameter of 3.3 μm, the antioxidant is antioxidant 264, and the compatibilizer is maleic anhydride grafted polyethylene, all of which are commercially available. The ethylene-vinyl alcohol copolymer is EVOH-1 in Table 3.
[0067] The above materials are first mixed and then kneaded in a vacuum kneading machine at 160-170°C to form a mold. They can then be coated on the outer periphery of the optical cable, or directly extruded or injection molded into a specific shape to obtain a corresponding packaging structure.
[0068] By replacing different polyurethane elastomers, the embodiments shown in Table 4 can be obtained.
[0069] Table 4
[0070]
[0071]
[0072] In the above embodiments, the polyurethane elastomer is adjusted. It can be seen that in this solution, the polyurethane structure formed by the combination of polycarbonate diol and saturated fatty acid polyester polyol has better softness and better overall mechanical properties than other solutions. In contrast, the solution using only polycarbonate has a larger overall hardness and poor tensile strength. The combination of polycarbonate polyester polyol and aromatic polyester polyol will also produce a larger hardness, and the tensile strength and transparency will decrease significantly after aging. The use of a single saturated fatty acid polyester polyol will result in a smaller hardness and a lower overall strength.
[0073] In addition, among the saturated fatty acid polyester polyols, polyethylene glycol sebacate has the best overall effect, but when its molecular weight is too large, the soft segment of the system will be too long, its moisture resistance will be significantly reduced, and the barrier property will be poor. The number average molecular weight of polycarbonate diol should be controlled at 2500-3000. Too large molecules will lead to low hardness and low transparency, while too small molecular weight will lead to a decrease in the mechanical strength of the system and a certain decrease in moisture resistance.
[0074] Furthermore, on the basis of Example 18, different ethylene-vinyl alcohol copolymers were used and the amount of ethylene-vinyl alcohol copolymer was adjusted, and the examples and experimental results shown in Table 5 were obtained.
[0075] Table 5
[0076]
[0077]
[0078] From the experimental results shown in Table 5, it can be seen that whether the ethylene-vinyl alcohol copolymer is replaced by high-density polyethylene, low-density polyethylene or ethylene-vinyl acetate copolymers of different grades, the transparency of the system will be significantly reduced after long-term use. Direct use of polyvinyl alcohol will result in a larger hardness of the system and deviation in processing performance. When the amount of polyvinyl alcohol added to the system reaches 30-40 parts, it is easier to form a continuous phase. The formation of the continuous phase of polyvinyl alcohol in the system will easily lead to unevenness inside, which will have a certain impact on the initial transparency. The specific gravity required for the continuous phase formation of the ethylene-vinyl alcohol copolymer system is larger, so the transparency of the system will only decrease after adding more than 40 parts.
[0079] Furthermore, based on Example 18, the terpene resin and ultra-low density polyethylene in the above packaging material were adjusted, and the experimental results were shown in Table 6.
[0080] Table 5
[0081]
[0082]
[0083] From the above experimental data, we can see that terpene resin plays an important role in enhancing cohesion in the system, and has less impact on transparency, will not agglomerate in the system, and thus has better effectiveness, and terpene resin can better form a coupling system with ethylene-vinyl alcohol copolymer, thereby improving the long-term moisture resistance in the packaging material system. Ultra-low density polyethylene has the effect of improving softness, so that the above system can still maintain the state of an elastomer, taking into account moisture resistance, aging resistance and soft properties, but excessive addition will lead to a decrease in its mechanical properties.
[0084] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A high-transmittance packaging material for optical communication equipment, characterized in that: The components include the following in parts by mass: Polyurethane elastomer 100 parts Terpene resin 1-3 parts Phosphorus-containing flame retardant 5-10 parts 30-40 parts of ethylene-vinyl alcohol copolymer Glass fiber 5-10 parts Antioxidant 0.1-1 part Compatibilizer 2-5 parts The polyurethane elastomer is obtained by polymerizing polyester polyol and aromatic isocyanate compounds, wherein the polyester polyol in the polyurethane elastomer comprises polycarbonate diol accounting for 30 to 50% of the mass of the polyester polyol; the polyester polyol is a combination of polycarbonate diol and saturated fatty acid polyester polyol; The isocyanate compound does not contain bromine atoms; The diameter of the glass fiber is less than 5 μm.
2. The high-transmittance packaging material for optical communication equipment according to claim 1, characterized in that: The number average molecular weight of the polycarbonate diol is 2500-3000.
3. The high-transmittance packaging material for optical communication equipment according to claim 1, characterized in that: In the ethylene-vinyl alcohol copolymer, the molar content of ethylene segments is 24-36%.
4. The high-transmittance packaging material for optical communication equipment according to claim 3, characterized in that: The number average molecular weight of the ethylene-vinyl alcohol copolymer is 30,000-36,000.
5. The high-transmittance packaging material for optical communication equipment according to claim 1, characterized in that: It also includes 10 to 15 parts by weight of ultra-low density polyethylene.
6. The high-transmittance packaging material for optical communication equipment according to claim 5, characterized in that: The saturated fatty acid polyester polyol is polyethylene glycol sebacate with double terminal hydroxyl groups.
7. The high-transmittance packaging material for optical communication equipment according to claim 6, characterized in that: The number average molecular weight of the polyethylene glycol sebacate is 650-800.
8. The high-transmittance packaging material for optical communication equipment according to claim 1, characterized in that: The phosphorus-containing flame retardant is polyphosphate.
9. The method for preparing a high-transmittance packaging material according to any one of claims 1 to 8, characterized in that: The method comprises the following steps: mixing the raw materials, kneading and forming the raw materials in a vacuum at 160-170° C. by a kneading machine, and then forming a corresponding packaging structure by any one of encapsulation, injection molding and extrusion.
Citation Information
Patent Citations
Environment-friendly TPU film for table mat and preparation method of environment-friendly TPU film
CN112239528A
Gas barrier laminate and packaging material
CN114025955A